Kepadatan Dan Persebaran Kepiting (Brachyura) Di Ekosistem Hutan Mangrove Segara Anakan Cilacap - Sri Redjeki; Mas’ad Arif; Retno Hartati; Laras Kinanti Pinandita (Jurnal Kelautan Tropis, 2017)
Segara Anakan area is a lagoon surrounded by mangrove forests and muddy land. Mangrove forests have an ecological function such as spawning ground, nursery ground, and feeding ground for various biota. The destruction of mangrove forests caused by human activities is quite alarming and affects the survival of living biota in it, one of them is crabs. Changes in the structure and composition of the crabs in mangrove ecosystems caused by habitat changes can be used as an indicator for water quality by biological index approach through population monitoring, community composition, or even the ecosystem function. So that, by the study of abundance and distribution of crabs on mangrove vegetation, the results can be used as monitoring of environmental conditions of mangrove ecosystems in Segara Anakan Area. This research was conducted to determine about the composition, abundance, diversity index, uniformity index, dominance index, and pattern of distribution of crabs on mangrove ecosystems in Segara Anakan, Cilacap. The sampling was conducted in July, 2016 in 3 locations namely Panikel, Bondan, and Kalibuntu. To determine the sampling location using random method of stratification. Crab sampling using 5m x 5m transect method in 3 stations with 3 repetitions at each station. The results of this research found 12 species consisting of 3 families of crabs. Ocypodidae Family is the most commonly crabs found in 3 location. The highest abundance of crab is in Kalibuntu (1,56 ind/m2) an the lowest abundance is in Panikel (1,27 ind/m2). There are two pattern of distribution of crabs in this research,  namely random and clumped. The diversity index values are in the medium category, whereas the uniformity index value is in the high category. In this research there is no dominance in all research location.